Preparation of Levulinic Acid Using Cellulase and Solid Acid Synergistic Hydrolysis for Rice Straw - Yu, Xian-Chun; Sun, De-Lin; Li, Xiang-Su (Asian Journal of Chemistry, 2010)
Levulinic acid was prepared from cellulase and SO4 2--TiO2/clay solid acid synergistic hydrolysis for rice straw. Orthogonal experiment and response surface methodology were applied to carry out optimum analysis on main parameters. The aim of this study is to obtain the optimal reaction conditions needed to degrade rice straw by cellulase and to synthesize levulinic acid with solid acid. The orthogonal experiment result shows that when the reaction temperature is 50 °C, the volume of the enzymolysis solution is 30 U g-1 of dried straw powder, the vibration reaction time is 8 h, the raw material granularity is 80 grit and the average content of reducing sugar is 15.67 mg mL-1. Response surface analysis indicates that under a reaction temperature of 215.94 °C, a reaction time of 34 min and a solid acid dosage of 7.10 %, the levulinic acid yield can reach 23.52 %. The synergistic hydrolysis of cellulase and SO4 2--TiO2/clay solid acid on rice straw had the benefit of increasing the levulinic acid yield. The existing reaction conditions are mainly the same as the experimental reaction conditions. As compared to the technology without the use of cellulase hydrolysis, the method in this study produced levulinic acid with 4.79 % increased yield.